ASUHAN KEPERAWATAN GERONTIK PADA LANSIA POST-STROKE DENGAN MASALAH RISIKO JATUH: STUDI KASUS - Rondonuwu, Junytha R; Momongan, Lieke; Gahunting, Niken (Lasalle Health Journal, 2024)
Introduction: Post-stroke is a phase experienced by patients after passing the critical phase of a stroke. Dangerous conditions that need to be monitored include the risk of falling because it can cause more dangerous impacts, namely a decline in function and physiological conditions that occur in the elderly phase. Nurses play an important role in providing nursing care to the elderly with post-stroke. Objective: This study aims to describe the application of gerontic nursing care for post-stroke patients at the "Damai" Ranomuut Nursing Home in Manado City. Method: A descriptive study using a case study method, referring to SDKI, SIKI, and SLKI. The subjects were 2 elderly post-stroke patients with the nursing problem of fall risk. Results: After providing nursing care for three consecutive days, the problem is partially resolved, namely a safe environment and being able to move around with assistance, although there is still a risk of falling. Interventions that still need to be continued gradually and have been taught to the caretakers of the orphanage include assisting respondents in carrying out independent activities and moving around without maximum assistance. Conclusion: The results of this study are expected to provide an overview of the implementation of nursing care for post-stroke elderly which is still not optimal for 3 days so that more time is needed and the implementation of other alternative collaborative actions/therapies based on evidence-based which must be taught to caregivers in nursing homes so that they can care for patients well.